2014
DOI: 10.1159/000358090
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation Associated with Pride and Shame

Abstract: Background: Self-referential emotions such as shame/guilt and pride provide evaluative information about persons themselves. In addition to emotional aspects, social and self-referential processes play a role in self-referential emotions. Prior studies have rather focused on comparing self-referential and other-referential processes of one valence, triggered mostly by external stimuli. In the current study, we aimed at investigating the valence-specific neural correlates of shame/guilt and pride, evoked by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 95 publications
1
29
0
3
Order By: Relevance
“…Our previous work studying brain responses to guilt scenarios showed that the guilt ratings were positively associated with activations in dorsal mPFC and supramarginal gyrus that is included in IPL [16]. Roth et al [17] investigated the neural correlates of autographical recall about shame and found that shame versus neutral condition elicited stronger activation in mPFC and PCC as well as weaker activation in IPL. Interestingly, studies on shame and guilt [15] have also reported findings in amygdala and dorsal anterior cingulate cortex (dACC) that are hyper-responsive in PTSD [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work studying brain responses to guilt scenarios showed that the guilt ratings were positively associated with activations in dorsal mPFC and supramarginal gyrus that is included in IPL [16]. Roth et al [17] investigated the neural correlates of autographical recall about shame and found that shame versus neutral condition elicited stronger activation in mPFC and PCC as well as weaker activation in IPL. Interestingly, studies on shame and guilt [15] have also reported findings in amygdala and dorsal anterior cingulate cortex (dACC) that are hyper-responsive in PTSD [18].…”
Section: Introductionmentioning
confidence: 99%
“…19 In one fMRI study, shame/guilt conditions, as well as pride, activated an emotional circuit including the amygdala, the insula, and the ventral striatum, and the bilateral dorsomedial prefrontal cortex. 68 In another study that attempted to disentangle the neural correlates of shame from guilt, both were associated with increased activations in the temporal lobes. However, shame activated most specifically the medial and inferior frontal gyrus, while guilt lead to greater activity in the amygdala and the insula.…”
Section: Psychology and Neurosciencementioning
confidence: 99%
“…In the present study, we used guilt and shame as examples to validate studying moral emotions by using fNIRS. Guilt and shame are two typical moral emotions, which have been extensively studied with functional magnetic resonance imaging (fMRI) (Takahashi et al, 2004;Finger et al, 2006;Moll et al, 2007;Wagner et al, 2011;Michl et al, 2012;Roth et al, 2014;Bastin et al, 2016;Zhu et al, 2019). We elicited the participants' guilt and shame experience using moral emotional context described by sentences.…”
Section: Introductionmentioning
confidence: 99%